La motivation scolaire d’élèves québécois du deuxième cycle du secondaire en temps de pandémie - Falardeau, Erick; Guay, Frédéric; Bradet, Richard; Boulet, Johannie (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
To understand how the distance education context resulting from COVID-19 is associated with adolescents’ academic motivation, we surveyed high school 3rd, 4th and 5th graders (14 to 17 years old) using two independent cohorts: one of 601 students, recruited in June 2020 and taught online; and the other of 3335 students, recruited in February 2021 and whom have received online education on alternating days for most of the school year. We compared the scores of these two cohorts with those of similar-aged students from a classroom study conducted in 2010 (n = 896). The results indicate significant differences between online and face-to-face teaching in terms of perceived competence, intrinsic motivation, identified extrinsic motivation and sense of belonging to their school. In addition, an eight-month follow-up with the June 2020 cohort shows that the differences increase over time.